2020
DOI: 10.1016/j.omtm.2019.12.004
|View full text |Cite
|
Sign up to set email alerts
|

AAV-Mediated CRISPR/Cas9 Gene Editing in Murine Phenylketonuria

Abstract: Phenylketonuria (PKU) due to recessively inherited phenylalanine hydroxylase (PAH) deficiency results in hyperphenylalaninemia, which is toxic to the central nervous system. Restriction of dietary phenylalanine intake remains the standard of PKU care and prevents the major neurologic manifestations of the disease, yet shortcomings of dietary therapy remain, including poor adherence to a difficult and unpalatable diet, an increased incidence of neuropsychiatric illness, and imperfect neurocognitive outcomes. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 56 publications
(66 reference statements)
1
84
0
Order By: Relevance
“…In previous study, we showed that inhibition of NHEJ enhances AAV-mediated gene repair. 4,33 Together these findings suggest that pharmacological stimulation of the FA pathway, particularly in combination with blockage of NHEJ, could be used to improve gene repair in hepatocytes.…”
Section: Discussionmentioning
confidence: 91%
“…In previous study, we showed that inhibition of NHEJ enhances AAV-mediated gene repair. 4,33 Together these findings suggest that pharmacological stimulation of the FA pathway, particularly in combination with blockage of NHEJ, could be used to improve gene repair in hepatocytes.…”
Section: Discussionmentioning
confidence: 91%
“… [ 127 ] Familial hypercholesterolemia Liver/hepatocyte Ldlr SpCas9 AAV8 2 vectors Subcutaneously injection at P1 Restored LDLR protein levels to 18.01 ± 2.82%. [ 128 ] Phenylketonuria (PKU) Liver/hepatocyte Pah SpCas9 AAV8 2 vectors i.v., facial vein at P3 Yielded around 10% HDR-corrected reads and reduced serum phenylalanine levels [ 129 ] Allelic exchange through HDR Hereditary tyrosinemia type I (HT1) and mucopolysaccharidosis type I (MPS1) Liver/hepatocyte Fah or Idua SpCas9 AAV8 or AAV9 2 vectors i.v., facial vein at P1; tail vein in adult mice Restored FAH activity in the liver from 0.4 to 1.6% of normal. Restored IDUA activity to ∼ 0.5% of the wild-type level, and substantially reduced GAG accumulation in the heart [ 130 ] HDR-mediated gene knock-in Hemophilia B Liver/hepatocyte hF9 at Rosa26 ZFN AAV8 2 vectors i.p.…”
Section: Broadening the Prospects Of Aav-delivered Therapeutics Throumentioning
confidence: 99%
“…The treatment significantly ameliorated atherosclerosis in mice fed with a high-fat diet [ 128 ]. In another study, newborn Pah enu2 mice, a disease model for phenylketonuria (PKU), intravenous delivery of AAV vectors carrying SpCas9, sgRNA, and donor DNA yielded significant correction of the mutations as well as reduction of serum phenylalanine levels [ 129 ].…”
Section: Broadening the Prospects Of Aav-delivered Therapeutics Throumentioning
confidence: 99%
“…Richard and co-workers (2020) have revealed the therapeutic significance of CRISPR/Cas9 technology for phenylketonuria treatment. 121 This disease is caused by the deficiency of phenylalanine hydroxylase due to which level of phenylalanine is raised, thus impairing the function of central nervous system. They used the adeno associated virus vector for the transmission of CRISPR/Cas9 machinery.…”
Section: Emerging Therapeutic Applications Of Crispr Technologymentioning
confidence: 99%